Engagement: Where to next?. (June 2016) - Eccles, Jacquelynne S.
Abstract: In my commentary, I discuss the historical origins of the Fredricks et al. 3 dimensions of engagement, provide some critical assessment of the individual papers in this special issue, and lay out the argument for renewed theoretical analysis of the concept of engagement. Specifically, the importance of theoretical work related to the definitions of engagement, dimensionality questions, and origins of, and influences, on engagement are discussed. Highlights: Historical origins of the Fredricks et al. 3 dimensions of engagement are presented. Strengths and limitations of papers in advancing our understanding of engagement are presented. Lays out argument for renewed attention to theoretical analysis of concept of engagement.